Use of an offset head center acetabular shell in difficult primary total hip arthroplasties - Wassef, Andrew J.; Khlopas, Anton; Sodhi, Nipun; Sultan, Assem A.; Piuzzi, Nicolas S.; Chughtai, Morad; Stearns, Kim L.; Molloy, Robert; Mont, Michael A. (Annals of Translational Medicine, 2018)
Several conditions may predispose patients to development of antero-lateral acetabular bone deficiency, including developmental dysplasia of the hip, osteonecrosis, or septic arthritis, among others. This may compromise the ability to gain acetabular component stability and impair reliable fixation. Large acetabular shells have often been used to achieve adequate fixation in scenarios of severe bone loss, however, these techniques have been shown to elevate the center of rotation (COR) of the hip and alter hip biomechanics. Recently, a new acetabular shell was developed with a goal of maintaining the native hip COR while achieving good fixation with standard instrumentation and technique. Previous radiographic studies have demonstrated the efficacy of this shell in lowering hip COR. In this case series, we demonstrate the use of this shell in patients with difficult hip pathologies. We have demonstrated how this offset COR acetabular shell may help bring down the COR of the hip in these quite challenging cases utilizing conventional techniques.